The life cycle of creative ideas: Towards a dual-process theory of ideation. (January 2021) - Gonçalves, Milene; Cash, Philip
Abstract : Ideation is simultaneously one of the most investigated and most intriguing aspects of design. The reasons for this attention are partly due to its importance in design and innovation, and partly due to an array of conflicting results and explanations. In this study, we develop an integrative perspective on individual ideation by combining cognitive and process-based views via dual-process theory. We present a protocol and network analysis of 31 ideation sessions, based on novice designers working individually, revealing the emergence of eight idea archetypes and a number of process features. Based on this, we propose the Dual-Process Ideation (DPI) Model, which links idea creation and idea judgement. This explains a number of previously contradictory results and offers testable predictive power. Highlights: We combine design process and cognitive views to understand ideation. We identify idea creation and idea judgement as two crucial dimensions to define ideas. We identify eight archetypal types of ideas. We propose a dual-process ideation model, linking idea creation and judgment. We provide a first step towards a dual-process theory of ideation.